Sensitization of Cervical Cancer Cells to Cisplatin by Genistein: The Role of NF?B and Akt/mTOR Signaling Pathways - Şahin, Kazım; Tuzcu, M.; Basak, N.; Caglayan, B.; Kilic, U.; Sahin, F.; Küçük, Ömer (Hindawi Ltd, 2012)
Cervical cancer is among the top causes of death from cancer in women. Cisplatin-based chemotherapy has been shown to improve survival; however, cisplatin treatment is associated with toxicity to healthy cells. Genistein has been used as an adjunct to chemotherapy to enhance the activity of chemotherapeutic agents without causing increased toxicity. The present study was designed to investigate the effect of genistein (25 mu M) on antitumor activity of cisplatin (250 nM) on HeLa cervical cancer cells. We have examined the alterations in expression of NF-kappa B, p-mTOR, p-p70S6K1, p-4E-BP1, and p-Akt protein levels in response to treatment. The combination of 25 mu Mgenistein with 250nM cisplatin resulted in significantly greater growth inhibition (P < 0.01). Genistein enhanced the antitumor activity of cisplatin and reduced the expression of NF-kappa B, p-mTOR, p-p70S6K1, p-4E-BP1, and p-Akt. The results in the present study suggest that genistein could enhance the activity of cisplatin via inhibition of NF-kappa B and Akt/mTOR pathways. Genistein is a promising nontoxic nutritional agent that may enhance treatment outcome in cervical cancer patients when given concomitantly with cisplatin. Clinical trials of genistein and cisplatin combination are warranted to test this hypothesis.
Keywords: Up-Regulation; Activation; Apoptosis; Resistance; Survival; Target; Growth; Agents; Contributes; Inhibition